THE ANALYSIS OF WASTE ACTIVITIES IN SUPRAMAK BED PRODUCTION BY USING VALUE STREAM MAPPING AND VALSAT APPROACHES - Dimaz Harits; Muhammad Ihsanul Aziz; Ari Andriyas Puji (Journal of Industrial Engineering Management, 2020)
X Ltd. is a company which is producing hospital equipment with one of its products is supramak bed (patient’s bed). From the observation at the production floor of X Ltd, several non-value added activities are identified, which are components accumulation, reworking a number of products which do not meet the standards, idling operators, and waiting in working process. Based on the results of VSM Current State Map is obtained that total time for value added activities are 96816 seconds and for non-value added activities are 80869 seconds. Based on WAM analysis, the highest waste occurs during waiting time with an index of 19.09%. Based on VALSAT analysis, the proposed input from researchers are as follows: giving the mandates to the warehouse department, monitoring product flow, creating and enforcing SOP, increasing the number of forklifts, and analyzing transportation effectiveness